Mongolia Public Expenditure and Financial Accountability : Performance Assessment Report 2021 - World Bank (World Bank, Washington, DC, 2021)
The objective of this PEFA assessment is to provide the Government of Mongolia (GoM) and its development partners with an objective, up-to-date diagnostic of the national-level public financial management (PFM) performance based on the latest PEFA methodology. The 2021 PEFA assessment is intended to provide an update of progress in PFM reforms since the last PEFA in 2015, and to establish a new PEFA baseline using the 2016 PEFA methodology. More specifically, this PEFA assessment (i) provides a clear and updated picture of Mongolia’s public finance systems and (ii) measures PFM systems, processes, and institutions that contribute to the achievement of desirable budget outcomes, aggregate fiscal discipline, strategic allocation of resources, and efficient service delivery. The PEFA assessment will (i) inform the government on areas of PFM strengths and weaknesses; (ii) facilitate and update the dialogue on the PFM action plan between the Government and development partners; (iii) support monitoring and evaluation of the Government’s PFM reform action plan by providing an updated performance baseline and relevant performance measures, and (iv) help development partners build budget support programs.